Design of a New Multilevel Inverter Standalone Hybrid PV/FC Power System. Issue 6 (3rd December 2015) - Venkateshkumar, M.; Raghavan, R.; Kumarappan, N.
Abstract: This paper analyzes different topologies of hybrid photovoltaic (PV)/fuel cell (FC) power system in standalone applications. Proposed topology with a compact conversion system using less number of power semiconductor, switches will improve hybrid system power quality. The MATLAB SIMULINK tool is utilized to design and develop the proposed system by which voltage regulators common coupling point voltage is controlled and regulated. Simulated results are compared with IEEE 1547 standard to authenticate the effectiveness of the proposed model. The proposed system will be implemented in real time prototype model. The real time prototype model results are compared with simulation results.